Elementary Linear Algebra : with Supplemental Applications - Anton, Howard; Rorres, Chris (New Delhi: Wiley, 2023)
Elementary Linear Algebra 11th edition gives an elementary treatment of linear algebra that is suitable for a first course for undergraduate students. The aim is to present the fundamentals of linear algebra in the clearest possible way; pedagogy is the main consideration. Calculus is not a prerequisite, but there are clearly labeled exercises and examples (which can be omitted without loss of continuity) for students who have studied calculus.
Includes Appendix, answers and index
Keywords: Linear Algebra; Matrix algebra; Determinants; Vector spaces; Linear transformations -- Application of mathematic